Refrigeration and air-conditioning technology course: sustainable growth of professional competency - Eugenio A. Ermac; Nolasco K. Malabago (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2013)
This study was conducted to explore a practical discussion on helping the students’ professional competency. More specifically, this study conducted two studies developing a competency analysis profile on refrigeration and air conditioning technology, and examining the essential core competencies for training undergraduate students in Bachelor of Science in Industrial Technology specializing Refrigeration and Air Conditioning Technology at Cebu Technological University. The qualitative and quantitative data were collected through observations, interviews, document analysis, and developing a curriculum job analysis process from six (6) training instructors from Cebu Technological University, two (2) training instructors from Technical Education Skills and Development Authority and three (3) service technicians from wellknownRefrigeration and Air Conditioning Service Centers in Metro Cebu. Moreover, the importance of core competencies as rated by respondents and the mean rating were calculated for each competency. The quality of the results had to be applied for a systematic curriculum and instructional development to effective implementation guidelines. Thus, enhance the competencies in Refrigeration and Air Conditioning Technology